Effect of bariatric surgery on glycemic and metabolic outcomes in people with obesity and type 2 diabetes mellitus: a systematic review, meta-analysis, and meta-evidence of 39 studies - Wei, Xiao; Yuan, Haijuan; Wang, Daorong; Zhao, Jing; Fang, Fang (Frontiers in Nutrition, 2025)
BackgroundBariatric surgery has become a widely utilized therapeutic approach for obesity management and glycemic regulation in individuals with type 2 diabetes mellitus (T2DM). This meta-analysis examines the effects of bariatric surgery on key glycemic and metabolic parameters.MethodsA systematic literature search was performed across PubMed, Scopus, Embase, and Web of Science to identify relevant studies assessing alterations in outcomes following bariatric surgery compared to baseline measurements. Eligible studies were analyzed using a random-effects model to compute weighted mean differences (WMD) and their corresponding 95% confidence intervals (CIs).ResultsBariatric surgery resulted in 39 with 3,855 participants in significant reductions in fasting blood glucose (FBG) (WMD: −0.82 mg/dL; 95%CI: −0.92 to −0.72), postprandial glucose (PPG) (WMD: −4.15 mg/dL; 95%CI: −5.38 to −2.92), Homeostatic Model Assessment for Insulin Resistance (HOMA-IR) levels (WMD: -2.81; 95% CI: −3.06 to −2.56), C-peptide (WMD: -0.38; 95%CI: −0.73 to −0.03) and fasting insulin (WMD: -0.62; 95% CI: −0.88 to −0.36). No significant reduction in glycated hemoglobin (HbA1c) levels was observed (WMD: -0.17; 95%CI: −0.39 to 0.04). Follow-up periods ranging from 2.3 to 120 months.ConclusionIt was concluded that the bariatric surgery may have improved the glycemic and metabolic outcomes. Therefore, the results underscore the value of incorporating bariatric surgery into diabetes care strategies, highlighting its potential to enhance long-term diabetes management and mitigate the risk of complications.